Canard Limit Cycle of the Holling-Tanner Model - Chongwu Zheng; Fengqin Zhang; Jianquan Li (Discrete Dynamics in Nature and Society)
By using the singular perturbation theory on canard cycles, we investigate the canard phenomenon for the Holling-Tanner model with the intrinsic growth rate of the predator small enough. The obtained result shows that there may be at most one canard limit cycle, and the range of small parameters is estimated. The phenomenon of outbreak is explained.